Mainstreaming the Sustainable Development Goals in developing countries - Dickens, Chris; Nhlengethwa, Sibusiso; Ndhlovu, Brown (International Water Management Institute, 2019)
The United Nations 2030 Agenda for Sustainable Development promises to achieve change in almost every aspect of life on Earth. Encompassing 17 Sustainable Development Goals (SDGs) and 169 targets, the Agenda marks the first time in history when all nations have agreed on how to chart their future. The SDGs are not just a global reporting exercise, however, but rather involve a global program that embraces country-led efforts. Guided by the ideas contained in the 2030 Agenda, each nation must seek to become more prosperous and sustainable, while contributing to the global effort at the same time. If all the countries achieve this, we will have a sustainable planet and a secure future for all. This document offers guidance on how developing countries can adapt the SDGs to their own contexts and priorities. It indicates important areas for developing countries to consider when creating their own program to achieve the SDGs, and provides examples of success to demonstrate concrete possibilities for progress.